Management of Bivalirudin Anticoagulation Therapy for Extracorporeal Membrane Oxygenation in Heparin-Induced Thrombocytopenia: A Case Report and a Systematic Review - Zhong, Han; Zhu, Ming-Li; Yu, Yue-Tian; Li, Wen; Xing, Shun-Peng; Zhao, Xian-Yuan; Wang, Wei-Jun; Gu, Zhi-Chun; Gao, Yuan (Frontiers in Pharmacology, 2020)
Extracorporeal membrane oxygenation (ECMO) can provide respiratory and cardiac support to patients in reversible devastated conditions. Heparin is the mainstay for anticoagulation during ECMO. Bivalirudin, a direct thrombin blocker, may represent an effective alternative for patients suffering from heparin-induced thrombocytopenia (HIT). We present the first case of a Chinese patient who experienced HIT and received bivalirudin anticoagulation during ECMO. In addition, we present a systematic review for this topic. We searched PubMed, EMBASE, and Cochrane Library (up to April 20, 2020) for studies that included patients undergoing ECMO, presenting with HIT, requiring bivalirudin treatment, and reporting relevant outcomes. The literature review yielded 15 studies involving 123 patients, amongst whom 58 patients were confirmed or suspected HIT patients, and 76 patients received bivalirudin as an anticoagulant for ECMO. Twelve studies were included for quantitative synthesis, and 46 patients were retrieved. The mean age of these patients was 46 years, and 30 patients were males. The average maintenance rate of bivalirudin was 0.27±0.37 mg/kg/h, in order to maintain a target of activated clotting time (ACT) of 160–220 s. Additionally, bivalirudin doses in patients with continuous renal replacement therapies (CRRT) and patients without CRRT were 0.15±0.06 mg/kg/h vs 0.28±0.36 mg/kg/h, respectively (p=0.15). Most of the patients with confirmed HIT improved platelet counts in 3.3±2.8 days after switching to bivalirudin anticoagulation. The patient-level data showed that 29 cases survived, 1 reported major bleeding, and 4 reported thrombotic events. Bivalirudin might be a promising optimal choice for ECMO anticoagulation in patients with HIT. A tailored protocol for management of bivalirudin treatment during ECMO should be developed with caution. Further prospective studies are necessary to standardise the use of bivalirudin.